Photocuring 3D printing modified aluminum oxide ceramic slurry and preparation method of ceramic core
Alumina ceramic slurry was prepared by sol-gel method and photopolymerization 3D printing technology, forming multi-scale interconnected pores and combined with low temperature liquid phase sintering, which solved the contradiction between high porosity and mechanical properties of ceramic core and improved the overall performance of ceramic core.
Patent Information
- Application Number
- CN202511038964.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-28
- Publication Date
- 2025-11-25
AI Technical Summary
Traditional ceramic core preparation technology suffers from problems such as long process cycle, high cost, low manufacturing precision, and difficulty in meeting the requirements of complex structures. Furthermore, it is difficult to balance high porosity and mechanical properties in alumina-based ceramic cores.
A pore-forming agent, CaCO3@SiO2, with a core-shell structure was formed using the sol-gel method. Alumina ceramic slurry was prepared by photopolymerization 3D printing technology. By combining low-temperature liquid phase sintering and lattice activation mechanisms, the formation of multi-scale interconnected pores and high densification were achieved, thereby improving mechanical properties.
This method achieves a balance between high porosity and high mechanical properties in alumina ceramic cores, improves the overall performance of ceramic cores, and solves the manufacturing efficiency and precision problems existing in traditional methods.
Abstract
Description
Technical Field
[0001] This invention relates to the field of additive manufacturing ceramic materials technology, and in particular to a method for preparing a photopolymerizable 3D printing modified alumina ceramic slurry and ceramic core. Background Technology
[0002] In the modern aerospace industry, turbine blades, as core components, operate under extreme high-temperature and high-pressure conditions, placing extremely stringent requirements on their performance. To improve the turbine blades' temperature resistance and operating efficiency, the design of complex internal cooling channels is becoming increasingly critical. This makes ceramic cores an indispensable component in the investment casting process of turbine blades. The quality and performance of the ceramic core directly affect the precision and yield rate of the turbine blades, thus impacting the overall performance and reliability of the aero-engine.
[0003] Alumina-based ceramic cores, with their outstanding advantages such as high melting point, excellent chemical stability, no phase change during use, and high positioning accuracy, have shown great application potential in the preparation of high-melting-point turbine blades, becoming a key material for the next generation of high-performance ceramic cores. However, traditional ceramic core preparation technologies, such as hot-press molding, have many drawbacks. This method is highly dependent on molds, and the entire process cycle, from mold design and manufacturing to final molding, is lengthy and costly. Moreover, facing the increasingly complex structural requirements of ceramic cores, traditional technologies are inadequate in terms of manufacturing precision and complex shape realization, making it difficult to meet the rapid development pace of the aerospace industry. Photopolymerization molding technology has significant advantages such as moldlessness, high precision, good surface quality, and high molding efficiency. It can accurately manufacture ceramic cores with complex internal structures and precise dimensions, making it particularly suitable for the production of components such as ceramic cores for aero-engine turbine blades, which have extremely high requirements for precision and structural complexity.
[0004] Because alumina has good resistance to acids and alkalis, chemical core removal is difficult. Although increasing the porosity can improve the core removal performance, it will reduce the bending strength of the ceramic core. How to balance the contradiction between high porosity and mechanical properties has become a key problem.
[0005] In view of the above-mentioned shortcomings, the inventors of this invention have proposed this invention after a long period of research and practice. Summary of the Invention
[0006] To address the shortcomings of existing technologies, this invention discloses a method for preparing photopolymerizable 3D printing modified alumina ceramic slurry and ceramic core. The technical solution of this invention solves the problem of balancing high porosity and mechanical properties in photopolymerizable 3D printing alumina-based ceramic cores, effectively improving the overall performance of the ceramic core.
[0007] Furthermore, the preparation method of the photopolymerizable 3D printing modified alumina ceramic slurry and ceramic core includes the following steps:
[0008] Step 1: Weigh CaCO3 powder and disperse it in deionized water. Adjust the pH to alkaline (9-10) by heating and stirring. Add sodium silicate solution dropwise to the above system. Simultaneously and slowly add dilute hydrochloric acid. Control the reaction temperature, stirring rate and reaction time so that SiO2 coats the surface of CaCO3 with chemical bonds (-Si-O-Ca-) to form a core-shell structure pore-forming agent CaCO3@SiO2.
[0009] Step 2: Mix the pore-forming agent CaCO3@SiO2 with alumina powder, add anhydrous ethanol as the dispersion medium, ball mill, dry and sieve to obtain modified alumina powder;
[0010] Step 3: Mix the modified alumina powder obtained in Step 2 with the photosensitive resin premix, and then ball mill it again to obtain a uniform photocurable 3D printing alumina ceramic slurry.
[0011] Step 4: Print the alumina ceramic slurry obtained in step 3 using a DLP printer, and obtain a high-precision alumina ceramic core blank by adjusting the molding parameters (exposure energy and slice thickness);
[0012] Step 5: Degrease the alumina ceramic core blank obtained in step 4 under vacuum to completely decompose the resin and pore-forming agent CaCO3@SiO2, forming interconnected pores.
[0013] Step 6: Transfer the degreased green body obtained in step 5 to a muffle furnace for sintering to obtain an alumina ceramic core with high porosity and high performance.
[0014] Furthermore, the amount of CaCO3 powder added in the first step is 2-10 wt.%.
[0015] Furthermore, the sodium silicate solution concentration in the first step is 5-20%, and the dilute hydrochloric acid concentration is 0.1-1M.
[0016] Furthermore, the reaction temperature in the first step is 50-80℃, the stirring rate is 200-500 r / min, and the reaction time is 1-3 h.
[0017] Furthermore, the alumina powder in the second step has an average particle size of 0.6 μm, and the mass percentage of Al2O3 powder is 90-98%.
[0018] Furthermore, in the second step, the ball mill speed is 100-300 r / min, and the ball milling time is 30 min-4 h.
[0019] Furthermore, the photosensitive premixed liquid in the third step comprises the following components by mass fraction: 70-90% photosensitive resin, 0.5-3% photoinitiator, 1-3 wt.% dispersant, and 10-30% plasticizer.
[0020] Furthermore, the photosensitive resin is selected from one or more of 1,6-hexanediol diacrylate, pentaerythritol tetraacrylate ethoxylate, acrylmorpholine, hydroxyethyl methacrylate, 2-phenoxyethyl acrylate, and o-phenoxyphenoxyethyl acrylate; the plasticizer is one or more of polyethylene glycol 200 and polypropylene glycol 200; the photoinitiator is one or more of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide; and the dispersant is one or more of BYK-111, dispersant BYK-180, and dispersant BYK-9076.
[0021] Furthermore, in the printing parameters described in step four, the exposure energy is 150-350 mJ / cm². 2 The slice thickness is 20-80μm.
[0022] Furthermore, the conditions for vacuum degreasing in step five are as follows: the first degreasing temperature is 130-180℃, the second degreasing temperature is 380-420℃, the third degreasing temperature is 550-650℃, the holding time is 60-180 min, and the heating rate is 0.5-3℃ / min.
[0023] Furthermore, the conditions for pressureless sintering in step six are as follows: the first sintering temperature is 900-1100℃, the second sintering temperature is 1400-1600℃, the holding time is 1-4h, the heating rate is 3-10℃ / min, and the cooling rate is 3-10℃ / min.
[0024] The beneficial effects of this invention are:
[0025] This invention provides a method for preparing photopolymerizable 3D printing modified alumina ceramic slurry and ceramic core. The method employs a sol-gel process, using sodium silicate (Na2SiO3) as the silicon source. Silicic acid (H2SiO3) is generated through acidification and then polymerized onto the surface of CaCO3 to form an amorphous SiO2 coating layer, ultimately forming a core-shell structured pore-forming agent, CaCO3@SiO2. During the degreasing stage (300-500℃), the outer shell SiO2 reacts with resin decomposition products to generate pore channels. During the sintering stage (above 1200℃), the inner core CaCO3 decomposes to generate CO2, creating secondary pores and forming multi-scale interconnected pores, thus improving the open porosity of the core. Secondly, during the sintering stage, the core CaCO3 will decompose into CaO, a sintering aid for alumina. This can form a low-melting-point compound at high temperatures, significantly reducing the liquid phase temperature. Through the dual mechanisms of low-temperature liquid phase sintering and lattice activation, the alumina ceramic can achieve low-temperature high densification, solving the problems of high energy consumption and grain coarsening caused by traditional high-temperature sintering, and improving the mechanical properties of the sintered alumina ceramic core. Detailed Implementation
[0026] To better understand the technical solution of the present invention, the present invention will be further described below with reference to specific embodiments. The following description is only a preferred embodiment of the present invention, but is not limited to the following embodiments and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
[0027] Example 1
[0028] A method for preparing a photopolymerizable 3D printing modified alumina ceramic slurry and ceramic core includes the following steps:
[0029] 6 wt.% CaCO3 powder was weighed and dispersed in deionized water. The pH was adjusted to alkaline by heating and stirring (9). Then, 5% sodium silicate and 0.5M dilute hydrochloric acid were added and stirred at 300 r / min for 2 h at 60 °C to obtain the core-shell pore-forming agent CaCO3@SiO2.
[0030] The prepared CaCO3@SiO2 and 94wt.%Al2O3 powders were placed in a ball mill jar and wet-milled for 3 hours with anhydrous ethanol as the medium. After drying and sieving, modified alumina powder was obtained.
[0031] 78 parts by weight of modified alumina powder and 22 parts by weight of photosensitive resin premix were added to a ball mill, and then the mixture was ball-milled at 1500 rpm for 5 minutes to obtain a modified alumina ceramic slurry. The photosensitive resin premix consisted of 8 parts by weight of 1,6-hexanediol diacrylate, 10 parts by weight of pentaerythritol tetraacrylate ethoxylate, 3 parts by weight of polyethylene glycol 200, 0.8 parts by weight of BYK-111, and 0.2 parts by weight of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.
[0032] The prepared modified alumina ceramic slurry was added to the DLP 3D printer, and a printing layer thickness of 50 μm and a printing speed of 200 mJ / cm were selected. 2 The exposure energy is used to form an alumina ceramic core blank. After printing, the residual slurry on the surface of the blank is removed from the printing platform and cleaned.
[0033] The printed ceramic core blank is placed in a vacuum degreasing furnace and heated to 150℃ at a rate of 1℃ / min and held for 60 min; then heated to 400℃ at a rate of 0.5℃ / min and held for 120 min; and finally heated to 600℃ at a rate of 0.5℃ / min and held for 120 min to complete the degreasing process of the blank.
[0034] The degreased green body is placed in a muffle furnace and heated to 1000°C at a rate of 10°C / min, and held for 2 hours; then heated to 1500°C at a rate of 5°C / min, and held for 4 hours; then cooled to 600°C at a rate of 6°C / min, and then cooled to room temperature with the furnace to obtain the ceramic core ceramic material.
[0035] The open porosity and flexural strength of the above ceramic core samples were tested. The results showed that the open porosity was 35.6% and the flexural strength was 49.4 MPa.
[0036] Example 2
[0037] A method for preparing a photopolymerizable 3D printing modified alumina ceramic slurry and ceramic core includes the following steps:
[0038] 8 wt.% CaCO3 powder was weighed and dispersed in deionized water. The pH was adjusted to alkaline by heating and stirring (10). Then, 10% sodium silicate and 0.2M dilute hydrochloric acid were added and stirred at 200 r / min for 3 h at 50 °C to obtain the core-shell pore-forming agent CaCO3@SiO2.
[0039] The prepared CaCO3@SiO2 and 94wt.%Al2O3 powders were placed in a ball mill jar and wet-milled for 4 hours with anhydrous ethanol as the medium. After drying and sieving, modified alumina powder was obtained.
[0040] 70 parts by weight of modified alumina powder and 30 parts by weight of photosensitive resin premix were added to a ball mill, and then the mixture was ball-milled at 1500 rpm for 5 minutes to obtain a modified alumina ceramic slurry. The photosensitive resin premix consisted of 12 parts by weight of pentaerythritol tetraacrylate ethoxylate, 8 parts by weight of pentaerythritol tetraacrylate ethoxylate, 2 parts by weight of polypropylene glycol 200, 0.5 parts by weight of BYK-180, and 0.2 parts by weight of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.
[0041] The prepared modified alumina ceramic slurry was added to the DLP 3D printer, and a printing layer thickness of 60 μm and a printing speed of 300 mJ / cm were selected. 2 The exposure energy is used to form an alumina ceramic core blank. After printing, the residual slurry on the surface of the blank is removed from the printing platform and cleaned.
[0042] The printed ceramic core blank is placed in a vacuum degreasing furnace and heated to 160℃ at a rate of 0.5℃ / min and held for 80 min; then heated to 380℃ at a rate of 1℃ / min and held for 60 min; and finally heated to 600℃ at a rate of 1℃ / min and held for 120 min to complete the degreasing process of the blank.
[0043] The degreased green body is placed in a muffle furnace and heated to 900°C at a rate of 5°C / min, and held for 2 hours; then heated to 1400°C at a rate of 5°C / min, and held for 2 hours; then cooled to 600°C at a rate of 5°C / min, and then cooled to room temperature with the furnace to obtain the ceramic core ceramic material.
[0044] The open porosity and flexural strength of the above ceramic core samples were tested. The results showed that the open porosity was 38.1% and the flexural strength was 45.2 MPa.
Claims
1. A method for preparing a photopolymerizable 3D printing modified alumina ceramic slurry and ceramic core, characterized in that, The preparation method includes the following steps: Step 1: Weigh CaCO3 powder and disperse it in deionized water. Adjust the pH to alkaline (9-10) by heating and stirring. Add sodium silicate solution dropwise to the above system. Simultaneously and slowly add dilute hydrochloric acid. Control the reaction temperature, stirring rate and reaction time so that SiO2 coats the surface of CaCO3 with chemical bonds (-Si-O-Ca-) to form a core-shell structure pore-forming agent CaCO3@SiO2. Step 2: Mix the pore-forming agent CaCO3@SiO2 with alumina powder, add anhydrous ethanol as the dispersion medium, ball mill, dry and sieve to obtain modified alumina powder; Step 3: Mix the modified alumina powder obtained in Step 2 with the photosensitive resin premix, and then ball mill it again to obtain a uniform photocurable 3D printing alumina ceramic slurry. Step 4: Print the alumina ceramic slurry obtained in step 3 using a DLP printer, and obtain a high-precision alumina ceramic core blank by adjusting the molding parameters (exposure energy and slice thickness); Step 5: The alumina ceramic core blank obtained in step 4 is degreased in a vacuum environment to completely decompose the resin and pore-forming agent CaCO3@SiO2, forming interconnected pores. Step 6: Transfer the degreased green body obtained in step 5 to a muffle furnace for sintering to obtain an alumina ceramic core with high porosity and high performance.
2. The method for preparing a photopolymerizable 3D printing modified alumina ceramic slurry and ceramic core according to claim 1, characterized in that, The amount of CaCO3 powder added in the first step is 2-10 wt.%, the concentration of sodium silicate solution is -20%, and the concentration of dilute hydrochloric acid is 0.1-1M.
3. The method for preparing a photopolymerizable 3D printing modified alumina ceramic slurry and ceramic core according to claim 1, characterized in that, The reaction temperature in the first step is 50-80℃, the stirring rate is 200-500r / min, and the reaction time is 1-3h.
4. The method for preparing a photopolymerizable 3D printing modified alumina ceramic slurry and ceramic core according to claim 1, characterized in that, The alumina powder in the second step has an average particle size of 0.6 μm, and the mass percentage of Al2O3 powder is 90-98%. The ball mill speed is 100-300 r / min, and the ball milling time is 30 min-4 h.
5. The method for preparing a photopolymerizable 3D printing modified alumina ceramic slurry and ceramic core according to claim 1, characterized in that, The photosensitive premixed liquid described in the third step comprises the following components by mass fraction: 70-90% photosensitive resin, 0.5-3% photoinitiator, 1-3 wt.% dispersant, and 10-30% plasticizer.
6. The method for preparing a photopolymerizable 3D printing modified alumina ceramic slurry and ceramic core according to claim 7, characterized in that, The photosensitive resin is selected from one or more of 1,6-hexanediol diacrylate, pentaerythritol tetraacrylate ethoxylate, acrylmorpholine, hydroxyethyl methacrylate, 2-phenoxyethyl acrylate, and o-phenoxyphenoxyethyl acrylate; the plasticizer is one or more of polyethylene glycol 200 and polypropylene glycol; the photoinitiator is one or more of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide; and the dispersant is one or more of BYK-111, dispersant BYK-180, and dispersant BYK-9076.
7. The method for preparing a photopolymerizable 3D printing modified alumina ceramic slurry and ceramic core according to claim 1, characterized in that, The exposure energy in the printing parameters described in step four is 150-350 mJ / cm. 2 The slice thickness is 20-80μm.
8. The method for preparing a photopolymerizable 3D printing modified alumina ceramic slurry and ceramic core according to claim 1, characterized in that, The conditions for vacuum degreasing in step 5 are as follows: the first degreasing temperature is 130-180℃, the second degreasing temperature is 380-420℃, the third degreasing temperature is 550-650℃, the holding time is 60-180min, and the heating rate is 0.5-3℃ / min.
9. The method for preparing a photopolymerizable 3D printing modified alumina ceramic slurry and ceramic core according to claim 1, characterized in that, The conditions for pressureless sintering described in step six are as follows: the first sintering temperature is 900-1100℃, the second sintering temperature is 1400-1600℃, the holding time is 1-4h, the heating rate is 3-10℃ / min, and the cooling rate is 3-10℃ / min.
10. A photopolymerizable 3D printed alumina ceramic core prepared by the preparation method according to any one of claims 1 to 10.